Development of performance indexes for analysis of global value chain: an application on tilapia production zones in Brazil - Ribeiro, Vinícius Souza (2020)
Brazilian aquaculture production has grown systematically over the last decade, with tilapia production as the main activity. This chain was the object of analysis of this thesis, which has as a general objective to analyze the business environments of some tilapia production zones in Brazil. Using primarily data from 463 Tilapia production units (TPUs) and four production zones (TPZs) of three regions of the country, the research made use of fuzzy logic to estimate indexes that comparatively analyze the business environment of these production areas. Based on the Global Value Chains (CGV) approach, the thesis developed 24 indicators, organized into four dimensions of analysis, used as inputs in a fuzzy inference system that estimated multidimensional business environment fuzzy indexes (BEFI). The analysis of indicators and indexes comparing the four zones, categorized as emerging and consolidated, in addition to classifying the business environments pointed out important issues related to production dynamics in these zones. Additionally, the research addressed general issues for the development of the chain as a whole. Such as the benefits of a proximity to other agri-food chains, institutional business environment and different governance arrangements. The thesis is structured in three articles, in the first two discussions were developed that seek to expand the field of research in CGV and contribute to fill gaps identified in the approach. In the last article the indices and results of the zones are discussed in comparative terms. Finally, the thesis presented its general limitations and contributions to a future research agenda that, in addition to other issues, seeks to promote an expansion of studies of a quantitative and firm-level nature in the field. And that also dialogue with shorter chains and/or in the initial phase of global insertion, especially in the Global South. Is the case of aquaculture chains that have a potential impact on such relevant issues as food safety and sustainable development.